(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Ayyubid state, which extended from 568 - 661 AH / 1173-1263, was an important stage in the history of Islamic steadfastness in the face of the Crusader invasion. The factor of steadfastness in the face of this invasion was the most important role of the Ayyubid state and its emergence. The emergence idea of Ayyubid state has the banner of Jihad to expel the invaders, which lasted during the reign of Salah al-Din. However, the continuation of adopting this idea vanished soon after the death of its founder Salah al-Din; his inheritors forgot the idea of ​​jihad, and engaged in internal conflicts and expansionist ambitions, which was the main cause of the failure of this state in addition to the reasons ,are no less important, discussed in this paper, including the situation of the Muslim world and its succession, which was supposed to be a supporter factor for other Islamic forces defending this Islamic world, including the Ayyubid state. On the contrary, this caliphate suffered from disintegration which was a weakness and pressure factor on these forces. In addition to other factors that were talked about in the paper that contributed significantly to the failure of this state, including the economic factor, religious factor and genetic factor. This paper also discussed the relationship between the Ayyubid state and the other Islamic forces, which was hostile rather than peaceful, which made them exhausted their forces and the forces of these Islamic countries.